Head-worn displays for healthcare and industry workers: A review of applications and design. Issue 154 (October 2021) - Schlosser, Paul D.; Matthews, Ben; Sanderson, Penelope M.
Highlights: Most HWD applications have been developed to instruct users during their work. The design of HWDs has received little attention in healthcare and industry. Randomized controlled trials and longitudinal studies are still rare. Previous design research could inform the creation of usable HWD applications. Abstract: Head-worn displays (HWDs) have been studied extensively in healthcare and industrial contexts over the past years. In this survey paper, we analyse the use of HWDs that do not occlude the view of the environment in those two domains. In addition, we explore researchers' approaches to the design of HWD applications. Across four databases we found 351 papers that describe HWD applications in healthcare or industrial contexts. All located papers were systematically categorized and a subset of 96 unique and influential papers was selected to be included in this survey paper. The paper offers three main contributions. First, we describe seven distinct groups of HWD use cases. Second, we show that papers seldom report that design principles, previous research, or user input have informed the design of HWD applications. Third, we illustrate similarities and key differences between HWD research in the healthcare and industrial domains and show that research in each domain has considerable relevance for the other. Based on the results of our analysis, we summarize recommendations for the design of HWD applications, and outline promising future research directions.